Criminal fraud and election disinformation : law and politics - Horder, Jeremy (Oxford : Oxford University Press, 2022)
'Criminal Fraud and Election Disinformation' is about the state's approach to fraud and distortion of the truth in politics, especially during election campaigns. Deliberate mischaracterisation of political opponents and their policies has always been a part of politics; however, lying, dishonesty, and distortion of the facts remain morally wrong and have the potential to obstruct important political interests. For example, a false or misleading claim publicised about an election candidate may lead someone to lose an election that they might otherwise have won. So, does - and should - the law seek to provide protection from the risk of this happening, by directly prohibiting the making of false or misleading political claims, or by obliging internet platforms to censor such content?
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on March 9, 2022).
Keywords: Elections -- Corrupt practices; Disinformation -- Political aspects; Communication in politics; Internet in political campaigns